Arthropod fauna associated with organic and conventional maize crop - Ortega, Mariana Araújo; dos Santos, Tássia Tuane Moreira; Fernandes , Paulo Marçal (Scientific Electronic Archives, 2021)
The corn crop has a marked sensitivity to biotic and abiotic stresses. As a control method, basically, transgenic plants have been used in association with chemical control. However, frequent applications of insecticides affect the conservation of biodiversity, and consequently, the natural regulation of insect populations. Thus, the objective of the work was to compare the diversity of arthropodofauna associated with the cultivation of corn in organic and conventional systems. The experiments were carried out at Fazenda Nossa Senhora Aparecida, in Hidrolândia/GO, in two areas: one in a consolidated organic system and the other in a conventional system. The organic area (1 ha) was sown with the Creole variety Palha Roxa and no type of cultural treatment was carried out. The conventional area (10 ha) was sown with a transgenic hybrid resistant to the herbicide glyphosate 30F53VYHR and two chemical fertilizers were applied, for planting and cover, two applications of herbicides and an application of insecticide. To survey the arthropodofauna, in each area, two collections were made with six pitfall soil traps. The first collection was carried out in the vegetative stage and the second in the reproductive stage, approximately at 35 and 80 days after planting, respectively. The traps were kept in the field for a week. In addition, a collection with entomological net was carried out in 10 plants chosen at random. The collected insects were stored in plastic pots containing 70% alcohol and taken to the laboratory for quantification and identification. The data referring to the total of insects collected were submitted to the T test at 5% probability. In the two collected with pitfall traps, the largest number of arthropods was collected in the area of ​​organic cultivation, with greater diversity of orders and families in this area. In the collection performed with entomological network, there was no difference between the places of cultivation. Organic crops provide better conditions for establishment and development for insects, especially those that spend some life in the soil. Therefore, the diversity of arthropods is greater in this cultivation system.